2022
DOI: 10.1021/acs.energyfuels.1c04051
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Heavy Metals during Pyrolysis and Gasification of Metal-Contaminated Waste Biomass: A Review

Abstract: The presence of contaminates (i.e., heavy metals) in biomass through various sources (industrial activities and municipal solid waste) from its growth to end use has become a nuisance. Over the past years, biofuel production from metal-contaminated waste biomasses (MCWBs) has attracted more attention on account of the potential roles in addressing both energy and environmental concerns. This review considers the migration and transfer behaviors of heavy metals into various output streams, including solid produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 158 publications
1
2
0
Order By: Relevance
“…In the present analysis, Cd and Ni are almost completely captured by the cyclone filter, and their content is negligible in the fugitive ashes. This result agrees only partially with a recent review about the assessment of HM during gasification process [43] in which it is shown how Cd and Ni have opposite behaviours: the first is easily transported away by the syngas, while the second tends to accumulate mainly in the bottom ash. In the case studied the olivine has influenced the emission of Ni, but the cyclone has represented an effective system of abatement for the fractions in which both Ni and Cd have concentrated.…”
Section: Table Iasupporting
confidence: 87%
“…In the present analysis, Cd and Ni are almost completely captured by the cyclone filter, and their content is negligible in the fugitive ashes. This result agrees only partially with a recent review about the assessment of HM during gasification process [43] in which it is shown how Cd and Ni have opposite behaviours: the first is easily transported away by the syngas, while the second tends to accumulate mainly in the bottom ash. In the case studied the olivine has influenced the emission of Ni, but the cyclone has represented an effective system of abatement for the fractions in which both Ni and Cd have concentrated.…”
Section: Table Iasupporting
confidence: 87%
“…A 10 g soil sample was selected from the area polluted by cadmium emitted by the nuclear plant, and was put into a conical flask with 90 mL sterilized liquid beef extract peptone with glass beads under a sterile environment. The obtained conical flask was placed into a shaker and shaken to obtain a uniformly mixed soil-liquid sample [8,9]. During the process, the shaking table speed and temperature were set to 150 rmp and 37 • C, and oscillated continuously for 12 h. The uniformly mixed soil-liquid sample was applied on different agar culture media, with 4 replicates set for each group.…”
Section: Materials Handling Methodsmentioning
confidence: 99%
“…Al-Afify et al analyzed water, sediment and two naturally growing plant samples collected seasonally from eight sites to investigate the level of heavy metal contamination in the Nile River. The results showed that cadmium and nickel contributed 80% and 10%, respectively, to the ecological risk assessment [8]. Fayuan W's team proposed the inoculation of soil with Mycorrhizal Fungi (AMF) for the purpose of heavy metal phytoremediation in response to heavy metal contamination in sweet sorghum.…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant heavy metals are calcium and silicon in food, paper, wood, yard and garden waste, railway ties, and biosolids [31]. These contaminants arise from the fertilization and pest control of crops as well as from the processing of materials and are harmful to the ecosystem [88]. In unmanaged landfills, there is the possibility for these metals to enter the food chain through the water system and/or soil.…”
Section: Contaminantsmentioning
confidence: 99%